THE CAUSE AND EFFECT ANALYSIS IN PRINTING MACHINE PROCESS OF THE MANUFACTURE OF CONTACT RUBBER SILICONE - Hendra Hendra; Yaman Parid; Hernadewita Hernadewita; Singgih Juniawan; Teuku Mirwan Saputra; D. Daruki (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
The automotive industry is a key pillar of the global economy. At present, the level of public needs is high in the field of motor vehicle equipment and components, the automotive world continues to experience competition and quality problems in its growth. This paper describes a project carried out by an automotive component industry company, to analyze the problem of reducing product defects in the contact rubber silicone printing process. Problems occur in the printing process such as product malfunction, poor appearance, and incorrect shape. The data before the repair was taken from January 2021 to August 2021. After analyzing and making improvements with the Six Sigma method approach, the result was a decrease in defective products seen in September 2021 - April 2022 with a decrease in defective products from 18,088 pcs to 211 pcs or 3.9 sigma to 5.2 sigma. The results of the analysis found that the cause of the problem occurred at the level of the ink print in the container which was less than 6 millimeters. The problem was fixed by installing the sensor as mistake-proofing. So that it can increase the company's profit due to the decrease in product failure.